2000
DOI: 10.1101/lm.7.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for a Dissociation Between Different Forms of Mnemonic Expressions in a Mouse Model of Age-related Cognitive Decline: Effects of Tacrine and S 17092, a Novel Prolyl Endopeptidase Inhibitor

Abstract: It has been demonstrated previously on the radial maze that the emergence of an age-related mnemonic impairment is critically dependent on the form which the discrimination problems took. Hence, when the arms were presented one by one (i.e., successive go-no-go discrimination), both adult and aged mice learned to distinguish between positive (baited) and negative (unbaited) arms readily, as evidenced by their increased readiness to enter positive relative to negative arms (i.e., by a differential in arm-entry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…It follows that the deleterious effect of age, and its reversal by RA, must be cognitive in nature. These contrasting effects should be taken as further evidence that these two versions of the position discrimination (i.e., stage 1 and stage 2) rely on distinct and dissociable memory systems Marighetto et al, 1999Marighetto et al, , 2000. The go-no-go discrimination in stage 1 involves separate unitary responses to individual arms and therefore can be achieved using elemental stimulus-response associations, forms of procedural and/or implicit memory that are independent of the hippocampal system.…”
Section: Effects Of Ra Administration On the Cognitive And Associatedmentioning
confidence: 99%
“…It follows that the deleterious effect of age, and its reversal by RA, must be cognitive in nature. These contrasting effects should be taken as further evidence that these two versions of the position discrimination (i.e., stage 1 and stage 2) rely on distinct and dissociable memory systems Marighetto et al, 1999Marighetto et al, , 2000. The go-no-go discrimination in stage 1 involves separate unitary responses to individual arms and therefore can be achieved using elemental stimulus-response associations, forms of procedural and/or implicit memory that are independent of the hippocampal system.…”
Section: Effects Of Ra Administration On the Cognitive And Associatedmentioning
confidence: 99%
“…7 A, B, 8A, B). This specific loss of mnemonic flexibility, revealed by a test situation demanding an explicit comparison between separately acquired information, has been proposed as a mouse model for the preferential declarative memory loss in senescence (Marighetto et al, 1999(Marighetto et al, , 2000 and in association with hippocampal dysfunction (Etchamendy et al, 2001(Etchamendy et al, , 2003Touzani et al, 2003;Mingaud et al, 2007). The deficit selectivity enables us to rule out trivial explanations (such as deterioration in motivation, perception, and locomotion) for observed changes in behavior (and concomitant brain activity, see below) in the aged mice.…”
Section: Hippocampal Retinoid Signaling Hypoexpression Is Associated mentioning
confidence: 99%
“…The identification of these substrates led to new hypotheses about Prep function, which were tested in vivo using pharmacological Prep inhibitors. Interestingly, several of these experiments suggested that Prep inhibition would lead to improved cognitive function in mammals, which was later verified (15)(16)(17)(18). However, the underlying mechanism for this improvement is still under investigation because some of the Prep substrates predicted to be responsible for this effect were unaffected, or only modestly affected, upon Prep inhibition (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The unique biochemical activity of Prep, namely the ability to cleave peptides at proline amino acids, has prompted a great deal of research into the biochemical, cellular, and physiological functions of this protein (9). In vitro assays have identified Prep substrates that range from the tripeptide, thyrotropin-releasing hormone, to a 31 amino acid peptide, beta endorphin (9,34), which led to new hypotheses about the physiological role of Prep, including a role in cognitive function (15)(16)(17)(18).…”
Section: Peptidomics Of Prep In the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation